EL ANÁLISIS AXIOLÓGICO COMO PROCESO SIGNIFICATIVO DE LA PSICOTERAPIA - Lanosa, Hernán (European Scientific Journal, ESJ, 2015)
The study of human values has realized the importance of personal development and guiding behavior. Rigorous research by Schwartz ( 1987, 1992 , 2000, 2004 ) implies a milestone in the field, since it shows that there are values that are replicated in different cultures which can be generalized . Such scientific finding opens the possibility for further study of human values , as well as generating processes, tools, techniques, and approaches that can enrich the work of psychology in general and psychotherapy particularly. This paper aims to present the proposal of "Axiological Analysis" which is nothing more than the analysis of personal values as a significant instance in the psychotherapeutic process.